Circuit Theory/Phasors/proof8

From Wikibooks, open books for an open world
Jump to: navigation, search
g(t)=G_m sin(\omega t - \phi)
g(t)=G_m cos(\omega t - \phi - \frac{\pi}{2})
g(t)=G_m \operatorname{Re}(e^{j(\omega t - \phi - \frac{\pi}{2})})
g(t)=G_m \operatorname{Re}(e^{j*(-\phi - \frac{\pi}{2})}e^{j\omega t})
g(t)=\operatorname{Re}(G_m e^{j*(-\phi - \frac{\pi}{2})}e^{j\omega t})
g(t)=\operatorname{Re}(\mathbb{G} e^{j\omega t})
\mathbb{G} = G_m e^{j*(-\phi - \frac{\pi}{2})} = G_m(cos(-\phi - \frac{\pi}{2}) + j*sin(-\phi - \frac{\pi}{2}))
 = G_m cos(-\phi - \frac{\pi}{2}) + j G_m sin(-\phi - \frac{\pi}{2})
 = G_m (cos(-\phi) cos(\frac{\pi}{2}) + sin(-\phi) sin(\frac{\pi}{2})) + j G_m (sin(-\phi)cos(\frac{\pi}{2})- cos(-\phi)sin(\frac{\pi}{2}))
 = G_m sin(-\phi) - j G_m cos(-\phi)
 = -G_m sin(\phi) - j G_m cos(\phi)